Standardization of Nursery Techniques of Acacia albida Del under North Indian Moist Climatic Condition - Bahuguna, V. K.; Maithani, G. P.; Dhaundiyal, U. C.; Unnikrishnan, K. P. (Indian Forester, 1987)
Acacia albida Del. is a multipurpose Sahelian Zone African tree. This tree is extensively used in Agro-foretry purpose. This species is belong introduced in Indian conditions. An investigation was taken up in tbe Nursery of Silviculture Branch of Forest Research Institute, Dehra Dun, to standardize its nursery tecbniques. For finding out the best combination of soil media and containers. The findings of this experiments are discussed in this paper.